FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN SEKTOR CONSUMER CYCLICALS - William Widjaja; Herlin Tundjung Setijaningsih (Jurnal Paradigma Akuntansi, 2026)
This study aims to analyze the effect of financial leverage, tax, and firm size on income smoothing at consumer cyclicals companies listed on the Indonesia Stock Exchange during the period of 2019-2021. This study uses 84 samples of consumer cyclicals companies with a total of 252 data for three years that were selected using the purposive sampling method. The data used in this study is secondary data obtained from the financial statements. Binary logistic regression was used to examine the relation between the dependent and independent variables and test the hypotheses. This study used IBM SPSS version 26 and Microsoft Excel 2016 to process the data. The result of this study is that financial leverage and firm size have a significant effect on the practice of income smoothing, while the tax has no significant effect on income smoothing. The implications of this study are as a reference source for other studies related to income smoothing practices supported by agency theory and positive accounting theory. This study also has implications as a consideration in investment decision-making for investors in the future.